P/q-Formel: Unterschied zwischen den Versionen
Aus KAS-Wiki
(DISPLAYTITLE) |
|||
Zeile 1: | Zeile 1: | ||
{{DISPLAYTITLE:p/q-Formel}} | {{DISPLAYTITLE:p/q-Formel}} | ||
<math>x=-\frac{p}{2} + \sqrt{( \frac{p}{2} )^2-q} \qquad \vee x=-\frac{p}{2} - \sqrt{( \frac{p}{2} )^2-q} | <math>x=-\frac{p}{2} + \sqrt{( \frac{p}{2} )^2-q} \qquad \vee x=-\frac{p}{2} - \sqrt{( \frac{p}{2} )^2-q} | ||
+ | |||
+ | |||
+ | [http://www.frustfrei-lernen.de/mathematik/pq-formel-quadratische-gleichungen-mathematik.html] |
Version vom 29. November 2011, 10:32 Uhr